MENINGKATAN DISIPLIN KERJA GURU DALAM MELENGKAPI ADMINISTRASI PENDIDIKAN MELALUI SUPERVISI KELAS - Kasnari . (Universitas PGRI Yogyakarta, 2016)
The purpose of this school action research is used to improve work discipline in completing the educational administration through classroom supervision for teachers atSDN 2 Nglandeyan in the second semester of the school year 2014/2015. As for the timeneeded to complete the research for 4 (four) months starting from the month of February2015 until May 2015 using a study in SDN 2 Nglandeyan Kedungtuban District of Blora. Inthis study using Action Research School (PTS) which is divided into two cycles andimplemented through four main activities that include planning (planning), action (acting),observation (observing) and reflection (reflecting) in every cycle , In the first cycle schoolprincipals encourage teachers to correct the deficiencies of education administration usingthe method of classroom supervision then a second cycle school principals encourageteachers to supplement the shortage of educational administration through methods ofclassroom supervision. The next action is a reflection of researchers work in improving theadministration of teacher education in the first cycle and cycle 2 and compared with theinitial conditions. From the result of reflection was found that the use of classroomsupervision method can be used by principals to improve the competence of teachers incompleting the educational administration in accordance with existing rules.Keywords: Supervision, Discipline and administration.